The data 37 Years of Moore's Law. - Adee, S.
From 2300 transistors on an Intel 4004 chip to the forest of 2 billion transistors residing on the latest generation of Intel microprocessors, Gordon E. Moore's famous law has guided the steady shrinking of transistors and their consequent density on microchips. That doubling about every two years is how we went from Pong in 1972 to the astonishing real-time rendering of hair that moves according to the laws of real-world physics in the video game Heavenly Sword in 2007. Technological advances like personal computers, the Internet, and video games drove these complementary slopes of cost decline and processing power growth. But just as in the chicken-and-the-egg scenario, those slopes were also the driving force behind the consequent technological advances.
Keywords: Intel microprocessors; Moore's law; Cost decline; Microchips; Processing power growth; Technological advances